Number theory: sailing on the sea of number theory : proceedings of the 4th China-Japan Seminar, Weihai, China Aug. 30-Sept 3, 2006 - Kanemitsu, Shigeru; Liu, J. Y. (Series on number theory and its applications, 2007)
This volume is not an ordinary proceedings volume assembling papers submitted but a collection of prestigious survey papers on various subjects studied enthusiastically by experts all over the world. The reader will uncover profound, new research problems as well as numerous signposts for future direction